Both Mating Types of Phaeosphaeria (anamorph Stagonospora) nodorum are present in Western Australia - Solomon, P.; Parker, K.; Loughman, R.; Oliver, Richard (2004)
Phaeosphaeria (anamorph Stagonospora) nodorum is the most serious fungal pathogen of wheat in the West Australian (WA) wheat belt and is a diallelic heterothallic loculoascomycete. Its population genetics has received considerable attention. A recent study, which sampled isolates from diverse locations worldwide, has indicated that the mating-type idiomorph MAT1-1 is considerably more frequent than MAT1-2 in many populations. To investigate this, we developed PCR primers that amplify each idiomorph. In a sample of 23 isolates cultured from ascospores collected in the field, nine amplified DNA with the MAT1-1 primers and 14 amplified DNA with the MAT1-2 primers. The virulence of a MAT1-2 isolate was comparable with MAT1-1 isolates. Although these sample sizes are small, we suggest that this result is consistent with the presence of equal numbers of both mating types in populations of ascospores in WA.